Dietary protein intake and prostate cancer risk in adults: A systematic review and dose-response meta-analysis of prospective cohort studies. (November 2022) - Alzahrani, Meshari A; Shakil Ahmad, Mohammad; Alkhamees, Mohammad; Aljuhayman, Ahmed; Binsaleh, Saleh; Tiwari, Rahul; Almannie, Raed
Abstract: Objective: This study aimed to conduct a comprehensive systematic review and dose-response meta-analysis to summarize available findings on the associations between dietary protein intake and prostate cancer risk as well as the dose-response associations of total, animal, plant, and dairy protein intake with prostate cancer risk. Methods: This study followed the 2020 PRISMA guideline. We conducted a systematic search in the online databases of PubMed, Scopus, ISI Web of Science, and Google Scholar to detect eligible prospective studies published to October 2021 that assessed total, animal, plant, and dairy protein intake in relation to prostate cancer risk. Results: Overall, 12 articles containing prospective studies with a total sample size of 388, 062 individuals and 30, 165 cases of prostate cancer were included. The overall relative risks (RRs) of prostate cancer, comparing the highest and lowest intakes of total, animal, plant, and dairy protein intake, were 0.99 (95% CI: 92–1.07, I 2 =12.8%), 0.99 (95% CI: 95–1.04, I 2 =0), 1.01 (95% CI: 96–1.06, I 2 =0), and 1.08 (95% CI: 1.00–1.16, I 2 =38.1%), respectively, indicating a significant positive association for dairy protein intake (P = 0.04) and non-significant associations for other protein types. However, this positive association was seen among men who consumed ≥ 30 gr/day of dairy protein, such that a 20 g/d increase in dairy protein intake (equal to 2.5 cups milk or yogurt) was associated with a 10% higher risk of prostate cancer (Pooled RR: 1.10, 95% CI: 1.02–1.20, I 2 = 42.5%). Such dose-response association was not seen for total, animal, and plant protein intake. Conclusion: Overall, dairy protein intake may increase the risk of prostate cancer in men who consumed > 30 gr/day of dairy protein. Larger, well-designed studies are still required to further evaluation of this association. Highlights: we found no significant association between total protein intake and risk of prostate cancer. Each increase of 20 gr/day of dairy protein was associated with a 10% higher risk of prostate cancer. The significant association between dairy and prostate cancer no longer held after excluding Allen et al. study.